2013
DOI: 10.1136/annrheumdis-2013-eular.1086
|View full text |Cite
|
Sign up to set email alerts
|

THU0558 Role of Physical Exercise in Patients with Hip Osteoarthritis

Abstract: Background Hip osteoarthritis evolution is slow, but progressive, with increasing degradation of the joint, worsening instability, with permanent pain and reduced walk perimeter. Objectives The purpose of this study was to examine the effects of a 3 weeks kinetic program on pain and the functional status of patients with hip osteoarthritis. Methods We conducted an observational, prospective, randomized study on a sample of 80 patients previously diagnosed with hip osteoarthritis. The patients were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Across all outcomes, 283 RCTs and 20 companion reports were included (citations in eReferences in the Supplement), with a total of 159 910 participants (mean age 78.1 years; 74% women). Two included studies were available only as conference abstracts, and 14 other studies were identified by scanning reference lists of included studies and relevant reviews …”
Section: Resultsmentioning
confidence: 99%
“…Across all outcomes, 283 RCTs and 20 companion reports were included (citations in eReferences in the Supplement), with a total of 159 910 participants (mean age 78.1 years; 74% women). Two included studies were available only as conference abstracts, and 14 other studies were identified by scanning reference lists of included studies and relevant reviews …”
Section: Resultsmentioning
confidence: 99%